Evidence on Changes in Aid Allocation Criteria - Claessens, Stijn; Cassimon, Danny; Van Campenhout, Bjorn (World Bank, 2012)
Have donors changed their aid-allocation criteria over the past three decades toward greater selectivity, a frequently stated goal of the international development community? Using data on how 22 donors allocated their bilateral aid among 147 countries over 1970–2004, the article finds that after the fall of the Berlin wall in 1989 and especially in the late 1990s, bilateral aid responded more to poverty and the quality of the policy and institutional environment in the recipient countries. Furthermore, the sensitivity of aid allocation to the country's size and its debt burden has declined over time. These results are robust to different samples and model specifications, various econometric techniques, and alternative measures of institutional quality. While the specific factors causing these changes cannot be identified—these presumably include geopolitical and economic concerns and the many changes in the international aid architecture—donors still differ greatly in their selectivity. This suggests that further, multifaceted reforms are needed to ensure even greater selectivity of aid.